2004
DOI: 10.1136/qshc.2003.008425
|View full text |Cite
|
Sign up to set email alerts
|

Communication failures in the operating room: an observational classification of recurrent types and effects

Abstract: Background: Ineffective team communication is frequently at the root of medical error. The objective of this study was to describe the characteristics of communication failures in the operating room (OR) and to classify their effects. This study was part of a larger project to develop a team checklist to improve communication in the OR. Methods: Trained observers recorded 90 hours of observation during 48 surgical procedures. Ninety four team members participated from anesthesia (16 staff, 6 fellows, 3 residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
485
3
14

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,104 publications
(511 citation statements)
references
References 17 publications
9
485
3
14
Order By: Relevance
“…Similarly, a communication event has been defined as a verbal or non-verbal exchange between two or more people (Lingard et al 2004). In the context of SoS, an organization communication interface exists when two or more communities of practices transmit and receive information correctly.…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a communication event has been defined as a verbal or non-verbal exchange between two or more people (Lingard et al 2004). In the context of SoS, an organization communication interface exists when two or more communities of practices transmit and receive information correctly.…”
Section: Communicationmentioning
confidence: 99%
“…The location and timing factors of communication refer to the physical and temporal situation of the interface (Lingard et al 2004). Lastly, content refers to the representation of information in the object used during the exchange and is divided technical and understanding concerns.…”
Section: Communicationmentioning
confidence: 99%
“…6 Lingard and colleagues found that communication failures were associated with factors such as delayed communication, incomplete and inaccurate content, exclusion of key individuals and issues left unresolved until the point of urgency. 6 One-third of the communication failures resulted in immediate effects, including inefficiency, team tension and procedural error.…”
Section: Casesmentioning
confidence: 99%
“…They do not take into account the fact that surgery and other 978-1-4244-2582-2/08/$25.00 c 2008 IEEE medical procedures are always performed as a team and thus, among the technical skills, require non-technical skills like communication, teamwork, leadership, and decision making [4]. Research indicates that failure in communication occurs in 30% of team exchanges and that one third of these failures results in situations putting the patient's life at risk [5]. To increase patient safety, training and improvement of communication among team members has to be an important aspect of clinical simulation.…”
Section: Introductionmentioning
confidence: 99%